PENGARUH PEMBERIAN KITOSAN TERHADAP UMUR SIMPAN MANGGA (Mangifera indica. L.) VARIETAS GEDONG GINCU - Mulyati, Neneng Sri; Sumarna, Pandu; juswadi, Juri; Asad, Faisal Al (Jurnal Agro Wiralodra, 2022)
Abstract Chitosan is one of the preservatives of food and fruit product. This study is aimed at recognizing the effects of natural preservatives kitosan with the age of saving mangoes (Mangifera indica, L.) gedong gincu varieties, and know the correct concentration of chitosan in saving mango age (Mangifera indica, L.) gedong gincu varieties the oldest one. The method do in this study is that of experimentation by using Rancangan Acak Lengkap (RAL) with the treatment of the six concentrations of kitosan (0%, 0,5%, 1,0%, 1,5%, 2,0%, and 2,5%) repeated four times on gedong gincu fruit that comes out red. Chitosan at different concentrations can have a noticeable effect on saving age, and it can extend saving age gedong gincu. Chitosan concentration 1,5%, on gedong gincu can extend saving age 5,9 day (6 day) from 6,97 day (7 day) to 12,87 day (13 day), when compared with the controls or without the chitosan and the weight 9,25%. This is happening because high respiration can be hampered by layers edible coating, meaning edible coating layer able of blocking water evaporation and respiration by closing the lentils and cuticle, so the weight shrink decreases. By giving the chitosan 1,5% can extend saving age of gedong gincu, thus reducing damage to the fruit (rotten) during the marketing process, this can increase the odds of selling, farmers' income, domestic mango traders, mango importers, and also increase competitiveness through prices competing in export markets.